The impact of operational factors on degradation of formaldehyde as a human carcinogen using Ag3 PO4 /TiO2 photocatalyst - Asghar Hadi; Aligholi Niaei; Azam Seifi; Yahya Rasoulzadeh (Tabriz University of Medical Sciences, 2023)
Background: The International Agency for Research on Cancer (IARC) identified formaldehyde as a carcinogen in 2004, yet formaldehyde is widely used in health care settings and various industries. In recent years, photocatalytic oxidation has been developed as a potential technique for removing pollutants arising from organic chemical agents and consequently promoting the health indices. This study investigated the effect of operational factors in optimizing formaldehyde removal from the air using Ag3 PO4 /TiO2 photocatalyst. Methods: An experimental study was designed to investigate the effect of operational factors on the efficiency of formaldehyde degradation. The variables investigated in this study include pollutant retention time, initial pollutant concentration and relative humidity. Sol-gel method was used to synthesize the nano-composite photocatalyst. An ideal experimental design was carried out based on Box-Behnken design (BBD) with response surface methodology (RSM). The sample size in this study includes all the glasses coated with Ag3 PO4 /TiO2 photocatalyst. Results: The maximum formaldehyde degradation of 32% was obtained at the initial concentration of 2 ppm, 20% relative humidity, and 90 minutes of retention time. Based on the statistical results, the correlation coefficient of the present study for the impact of operational factors on formaldehyde degradation was 0.9635, which means that there is only 3.65% probability of error in the model. Conclusion: The operational factors examined in this study (retention time, relative humidity, and initial formaldehyde concentration) were significantly influential in the degradation efficiency of formaldehyde by the photocatalyst. Due to the high exposure of employees and clients of health and treatment centers to formaldehyde as a carcinogenic substance, the results of this study can be used in ventilation systems to remove environmental pollutants in health care centers and other occupational settings.